Tensions of nationalism: The Mzabi student missions in Tunis and the politics of anticolonialism - Ghazal, Amal N. (International Journal of Middle East Studies, 2015)
Abstract This article examines the significant yet largely overlooked role of the Mzabis, a community from the northern edges of the Algerian desert, in Algerian and Tunisian anticolonialism and nationalism. In so doing, it pursues two aims: first, to shed light on the importance of Tunis to the politicization of the Mzabis in the 1920s and to their induction into local and regional anticolonial and national movements; and second, to highlight the tensions of subsuming regional identities into overarching national identities by focusing on Mzabi political activists’ negotiation of the relationship between the Mzab and Algeria as a national project. The article also explores the spectrum of political possibilities and alternatives envisioned by Mzabis as they participated in religious reform, anticolonial, and nationalist movements. This spectrum, I argue, conveys the fluid relationship between local, national, and regional identities, thus undermining teleological readings of national identity formation.
Keywords: Réformisme -- Mzab

Omani Fatwas and Zanzibari Cosmopolitanism: Modernity and Religious Authority in the Indian Ocean - Ghazal, Amal N. (The Muslim World, 2015)
Keywords: Réformisme -- Zanzibar

Lamkī, Aḥmad al- - Ghazal, Amal N. (Encyclopaedia of Islam, 2015)
Keywords: Biographies -- Oman

Politics and Polemics. Ibāḍī Theology in North Africa in the Modern Period - Ghazal, Amal N. (Ibadi theology: rereading sources and scholarly works, 2015)
Keywords: Réformisme

Ibadi Jurisprudence: Responses to Modernity - Ghazal, Amal N. (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Fiqh